Fabrication and Nanomechanical Characterization of Thermoplastic Biocomposites Based on Chemically Treated Lignocellulosic Biomass for Surface Engineering Applications - Sulaiman, Muhammad; Iqbal, Tanveer; Yasin, Saima; Mahmood, Hamayoun; Shakeel, Ahmad (Frontiers in Materials, 2021)
Diverse applications of polymeric materials have prompted development of eco-friendly, efficient and economical materials. These characteristics can be obtained by incorporating appropriate fillers in the polymeric matrix. The objective of this research is to investigate the impact of aqueous glycerol treated rice husk (RH) on surface mechanical properties of biocomposites. RH was treated with aqueous glycerol (75 wt.%) and compounded with low density polyethylene (LDPE) at different loadings (10, 20 and 30 wt.%). The resulting mixture was thermally pressed in molds to fabricate biocomposites. Mechanical and structural properties of untreated and treated RH are reported based on nanoindentation response and fourier transform infrared spectroscopy (FTIR) techniques. Surface mechanical properties such as elastic modulus, hardness, creep rate and plasticity index (H /E) of biocomposites reinforced with untreated and treated RH were investigated using nanoindenter. Experimental values depicted that hardness (H) and elastic modulus (Es) of treated biocomposites were lower than untreated biocomposites. Hardness (0.037 GPa) and elastic modulus (0.671 GPa) of treated biocomposites were obtained at biomass loading of 20 wt.%. A reduction in the creep rate by 20% and 14% were observed for the untreated and the treated biocomposites, respectively, in comparison to the neat polymeric sheet. An improvement in the plasticity index has also been reported for the biocomposites containing glycerol treated RH. The study indicated that aqueous glycerol pretreatment can partially strip off non-cellulosic constituents from lignocellulose matrix to generate cellulose-rich pulp for engineered composite applications.